Мемуар Григорія Орлика 1743 року - Траттнер, М.; Мушар, Ф. (Сiверянський літопис, 2023)
У публікації вперше представлений переклад українською мовою підготовленого послом Франції у Стокгольмі маркізом де Ланмарі для шведського уряду переказу мемуару Григорія Орлика 1743 р. Цей документ у лаконічній формі передає головні біографічні відомості про гетьмана Пилипа Орлика, а також оповідає про його заслуги перед Україною та Швецією. Мемуар був укладений з метою надання фінансової допомоги родині Орликів. У цьому документі є багато важливих подробиць для розуміння стратегії дій відомого мазепинця в еміграції. For the first time, the publication presents a translation into Ukrainian of the retelling of Hryhoriy Orlykʼs memoir of 1743, which was prepared by the French ambassador in Stockholm, the Marquis de Lanmarie, for the Swedish government. This document concisely provides the main biographical information about hetman Pylyp Orlyk, as well as tells about his services to Ukraine and Sweden. The memoir was prepared in order to provide financial assistance to the Orlyk family. This document contains many important details for understanding the strategy of actions of the famous mazepynets in exile.